Reaching hard-to-reach people through digital means – Citizens as initiators of co-creation in public services - Jalonen Harri; Kokkola Jussi; Laihonen Harri; Kirjavainen Hanna; Kaartemo Valtteri; Vähämaa Miika (Emerald, 2025)
Purpose – This paper considers the potential of social media for developing public services. The paper
approaches social media as a context that can provide information that might otherwise be unattainable. The
focus of analysis is on a special hard-to-reach group of marginalized youths who appear to have isolated
themselves from society.
Design/methodology/approach – The authors answer the question: How can the experiences of socially
withdrawn youth as shared on social media be used to enrich the knowledge base relating to the initiation phase of co-creation of public services? The data retrieved from the Finnish discussion forum are analyzed using the combination of unsupervised machine learning and discourse analysis.
Findings – The paper contributes by outlining a method that can be applied to identify expertise-byexperience
from digital stories shared by marginalized youths. To overcome the challenges of making socially
withdrawn youths real contributors to the co-creation of public services, this paper suggests several theoretical and managerial implications.
Originality/value – Co-creation assumes an interactive and dynamic relationship where value is created at
the nexus of interaction. However, the evidence base for successful co-creation, particularly with digital technology, is limited. This paper fills the gap by providing findings from a case study that investigated how social media discussions can be a stimulus to enrich the knowledge base of the co-creation of public services.